Enhanced negation handling for sentiment analysis on Twitter using deep neural networks - Mamatha Mylarappa; Shiva Kumar B. N; Thriveni J. Gowda; Venugopal K. Rajuk (Institute of Advanced Engineering and Science, 2023)
Sentiment analysis is a tool to identify and measure the emotion in a piece of text. Negation handling is an important aspect of natural language processing (NLP) for Twitter data. It is a process of correctly interpreting the sentences containing negation words, such as,